SOURCES OF CAPITAL FORMATION OF MODERN ENTERPRISES IN THE CONTEXT OF ENSURING THEIR FINANCIAL STABILITY (INNOVATIVE ECONOMY, 2024)
Vodolazska O.A., Holub Ye.О. SOURCES OF CAPITAL FORMATION OF MODERN ENTERPRISES IN THE CONTEXT OF ENSURING THEIR FINANCIAL STABILITYPurpose. The aim of the article is to study the peculiarities of capital formation of modern enterprises, to establish the advantages and disadvantages of internal and external financing, which will ensure a rational choice of sources of capital formation and increase the financial stability of enterprises.Methodology of research. The methods of analysis and synthesis were used in the work to determine the criteria for the application of forms of financing of modern enterprises. The method of generalization made it possible to establish the main advantages and disadvantages of using separate sources of capital formation of enterprises. Comparisons and graphic methods are used to clarify the current state of financing of Ukrainian enterprises. Findings. It was established that the use of only own capital limits and inhibits the development of modern enterprises, and this requires a transition to financing through borrowed funds. However, attracting external sources requires more creative and dedicated financial management. It is argued that taking into account the advantages and disadvantages of internal and external financing should create conditions for ensuring both the current solvency of enterprises and long-term financial stability.Originality. The criteria for the application of forms of financing of modern enterprises are summarized, taking into account the time of investment of capital, the sources of its attraction and the legal status of the person who provided the capital. The advantages and disadvantages of individual sources of capital formation are determined, which will allow to create competitive advantages for the enterprise in the future through the optimization of its capital structure from the point of view of efficiency and riskiness of involvement.Practical value. The theoretical and methodological provisions of this study deepen the practical tools of the application of individual forms of capital financing, taking into account their impact on the level of financial stability of modern enterprises.Key words: external and internal financing, equity capital, borrowed capital, credit, leasing.
Keywords: external and internal financing; equity capital; borrowed capital; credit; leasing.